Phytochemical evaluation of leaves, stems and inflorescences of Piper tuberculatum e Piper hispidum (Research, Society and Development, 2022)
The Piper genus is widely used for the most different purposes, therefore, phytochemical deepening is necessary. This work aimed to identify the metabolites of leaves, stems and inflorescences of Piper tuberculatum and Piper hispidum. The plant material was obtained in the experimental field and evaluated in the phytopathology laboratory at Embrapa Rondônia. The presence of alkaloids was confirmed in all samples when using the Dragendorff reagent, presence of saponins in leaves and stems of P. tuberculatum and stems of P. hispidum, flavonoids in all parts of P. tuberculatum and stems and inflorescence of P. hispidum, tannins, coumarins were found in all samples, phenolic compounds were observed in leaves of P. tuberculatum and leaves and inflorescence of P. hispidum, triterpenes were found in stalks and inflorescences of P. tuberculatum and P. hispidum. Both P. tuberculatum and P. hispidum showed a wide range of compounds.